Compound odontoma in the anterior region of the mandible (Research, Society and Development, 2023)
Introduction: Odontogenic tumors are classified according to their epithelial and/or ectomesenchymal origin. Odontoma has an incidence of 22 to 67%, thus being the most frequently reported odontogenic tumor in the oral cavity. Compound Odontoma is a generally asymptomatic benign tumor that originates from exaggerated proliferation of the lamina dura. It affects patients of all age groups and more males than females. The diagnosis of Compound and Complex Odontoma is confirmed through the evaluation of imaging tests and clinical examination. The treatment is surgical and, in many cases, it is easily removed. Among the consequences caused by Odontomas, there is the retention of permanent teeth. Case Report: Male patient, 20 years old, feoderm, attended a private clinic located in the municipality of Vitória da Conquista, with the aim of performing orthodontic treatment. After the intraoral physical examination, a panoramic radiograph was requested as the first imaging exam, when evaluating this exam, in the anterior region of the mandible a radiopaque image similar to a compound odontoma was observed, from this it was necessary to request a cone beam computed tomography between dental elements 42 and 43. After tomographic analysis, the diagnostic hypothesis of compound odontoma without association with impaction of permanent teeth was raised. The treatment of the lesion proposed to the patient was the exeresis of the lesion with preservation of the surrounding tissues. Conclusion: The enucleation of the lesion with the preservation of the hard and soft tissues is important for the maintenance of the masticatory function, aesthetics and phonation for the patient. This is established by carrying out clinical examinations associated with imaging tests, which contribute to a more reliable diagnosis, surgical and/or orthodontic planning and the predictability of a favorable prognosis. Furthermore, it is up to the dental surgeon to request complementary exams for carrying out the dental consultation, as lesions in the oral cavity may not be observed during intra and extraoral physical examination, but in imaging exams.